The application of the doctrine of caveat emptor in sale transaction in Malaysia. / Nur Huwaina Husna Rozaini, Shahirah AliZaman and Nur Faizura Ishak - Rozaini, Nur Huwaina Husna; AliZaman, Shahirah; Ishak, Nur Faizura (2013)
This research aims to discuss the application of the doctrine of caveat emptor in sale transactions in Malaysia. Its purpose is to educate the people about their rights as a buyer. In order to do so, statutory provisions such as the Sale of Goods Act 1957 and the Consumer Protection Act 1999 are analyzed and related cases are discussed. In addition, the paper also looks at the laws in the UK and the US with the aims of finding the best reforms of the law in Malaysia. This is because of the ambiguity of the law in its application regarding the doctrine of caveat emptor. Thus, the existing laws need to be improved to provide better protection to the consumers in Malaysia. This research paper also analyzes the awareness of consumers in Malaysia on the application of the doctrine. To do so, we questionnaires are distributed and the results reveal that most consumers are unaware of this doctrine although a majority of them answered they know of their rights as consumers. Hence, this paper made some recommendations to improve the existing law in order to protect the consumers and also to increase their awareness on their rights when purchasing goods.